Designing a guidebook of the English vocabulary and grammar list for junior high school students - Supriani, Nanik; Aguilar, Mark Gabriel Wagan; Khosiyono, Banun Havifah Cahyo; Mundilarno, Mundilarno; Agus, Wira Tunggul Segara; Sulaimon, Jamiu Temitope (Universitas Sarjanawiyata Tamansiswa, 2022)
The study aims at designing the stakeholders on the Guide book of vocabulary and grammar of English list for junior high school students. The background relied on the fact of implementing the 2013 curriculum. The students empirically had difficulty in facing the English examination since a lot of vocabulary was not well-instructed and issued at the test items. The list of vocabulary was difficult to find, and the grammar points were not complete, which determined the reading difficulty. Utilizing a descriptive-quantitative research design, a survey with open-ended questions and a focused-group discussion was done in terms of stakeholders, particularly students, teachers, and assessment instrument involvement. The findings showed that the deliberation included adding and deleting a few parts for improvement purposes, in which they had approved the one designed and presented. The finished product focused on the most important aspects of the vocabulary class, such as the characteristics of the vocabulary glossary, instructions for the guidebook use, and grammar list for the seventh- and eighth-graders. This guidebook serves as a model for the empirical learning circumstance, although it cannot be generalizable.